Recurrent synovial chondromatosis of the foot - Hossain, MA; Islam, M; Yeasmin, S; Nahar, N (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 316-319 The abstract of this article is available on the PubMed website